A history of Bangladesh - Schendel, Willem van (Cambridge, United Kingdom ; New York : Cambridge University Press, 2020)
"This is a book about the amazing twists and turns that have produced contemporary Bangladeshi society. It is intended for general readers and for students who are beginning to study the subject. Those who are familiar with the story will find my account highly selective. My aim has been to present an overview and to help readers get a sense of how Bangladesh came to be what it is today. How to write a history of Bangladesh? At first glance, the country does not seem to have much of a history. In 1930 not even the boldest visionary could have imagined it, and by 1950 it was merely a gleam in the eyes of a few activists. Only in the 1970s did Bangladesh emerge as a state and a nation. There was nothing preordained about this emergence - in fact, it took most people by surprise. Even so, you cannot make sense of contemporary Bangladesh unless you understand its history long before those last few decades. How have long-term processes shaped the society that we know as Bangladesh today? It is a complicated and spectacular tale even if you follow only a few main threads, as I have done. I have greatly compressed the story. To give you an idea: each page of this book stands for about a million people who have historically lived in what is now Bangladesh. This is, by any standard, a huge society folded into a small area. More people live here than in Russia or Japan. Bangladesh is the eighth most populous country on earth."--
Part I: The Long View -- A land of water and silt -- Jungle, fields, cities and states -- A region of multiple frontiers -- The delta as a cross roads -- Part II: Colonial Encounters -- From the Mughal empire to the British Empire -- British legacies -- A closing agrarian frontier -- Colonial conflicts -- Towards Partition -- Partition -- Population exchange -- Part III: Becoming East Pakistan -- The Pakistan experiment -- Pakistan falls apart -- East Pakistani livelihoods -- The roots of aid dependence -- A new elite and cultural renewal -- Part IV: War and the Birth of Bangladesh -- Armed conflict -- A state is born -- Imagining a new nation -- Part V: Independent Bangladesh -- Shaping a political system -- The triumph of identity politics -- Transnational linkages -- Boom or bust? -- Gender movements -- A national culture?
Includes bibliographical references and index.
GenEd
Keywords: Bangladesh -- History